2023
DOI: 10.3390/jmse11010184
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Benthic Scavenger Assemblages, a Multi-Habitat Approach in NW Iberian Peninsula

Abstract: Scavenging fauna plays an integral role in ecosystem functioning, nutrient cycling and circulating organic matter. Thus, baseline data of scavenger assemblages on the NW coast of the Iberian Peninsula that provides information on the abundance of species in different habitats is crucial to understanding the distribution of this understudied group. Two different types of baited traps, to capture scavenging megafaunal and scavenging benthopelagic macrofaunal assemblages, were deployed to compare them among rocky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Cirolana spp. has also been isolated from the ventral surface of deep-sea shark (Heptranchias perlo) from the Bahamas [26]. Finally, isopod scavenging has been reported in the coelomic cavity, on the external surface of organs (liver), and inside the esophagus and skull (salt gland) [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cirolana spp. has also been isolated from the ventral surface of deep-sea shark (Heptranchias perlo) from the Bahamas [26]. Finally, isopod scavenging has been reported in the coelomic cavity, on the external surface of organs (liver), and inside the esophagus and skull (salt gland) [2].…”
Section: Discussionmentioning
confidence: 99%
“…Bruce indicated that cirolanids are scavengers and predators that attach to fish from which they extract their nutrients and kill confined fishes [25]. Under favorable conditions, Cirolana fluviatilis becomes a serious pest and can cause mass mortality in cage-cultured finfish [26]. On the other hand, Keable considered Natatolana, one of the cirolanid species, as an opportunistic and voracious scavenger [27] because they usually swarm in large numbers and attack damaged fish, especially at dusk or during the night [28].…”
Section: Discussionmentioning
confidence: 99%